Generic formulations of imatinib for treatment of Philadelphia chromosome-positive leukemia in pediatric patients - Suttorp, Meinolf; Metzler, Markus; Millot, Frederic; Shimada, Hiroyuki; Bansal, Deepak; Günes, Adalet Meral; Kalwak, Krzysztof; Sedlacek, Petr; Baruchel, Andre; Biondi, Andrea; Hijiya, Nobuko; Schultz, Kirk R; et al. (Pediatric blood & cancer, 2018)
Since the patent for imatinib has expired, the role of generic imatinib (GI) in the management of Philadelphia chromosome-positive (Ph+) leukemia in pediatric patients has had ongoing discussion. Some studies in adults demonstrated that equivalent doses of GI and branded imatinib (BI) result in comparable plasma concentrations and clinical efficacy. However, other studies found that GI users are more likely to stop imatinib, with intolerance and decreased persistence as the main causes. Economic factors also heavily influence GI selection. This article aims to review the present knowledge to support further discussion on the role of GI in the management of pediatric Ph+ leukemia.
Keywords: tyrosine kinase; Humans; inhibitory proteinkinas; imatinib mesylát; dítě; generika; Child; imatinib inhibitor; Imatinib Mesylate; Female; Antineoplastic Agents; Ph+ leukemia; lidé; Protein Kinase Inhibitors; ženské pohlaví; generic medication; Male; chronická myeloidní leukemie; protinádorové látky; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Drugs, Generic; pediatric